Evaluation of phytochemical composition of aqueous extract of Annona reticulata and assessment of its neuroprotective activity on Paraquat-induced neurodegeneration in Drosophila melanogaster Oregon R - Shubha; Vaibhavi Bhardwaj; Naomi Varghese; Sowmya Kumar (Brain Disorders)
Neurons are essential for maintaining physiological balance, and abnormalities in neuronal activity or communication can lead to medical disorders. The term “neurodegenerative diseases” refers to a broad category of neurological disorders that affect different subsets of neurons in different functional anatomical systems. The term “neurodegenerative diseases” refers to a broad category of neurological disorders that affect different subsets of neurons in different functional anatomical systems. The Oregon R strain of Drosophila melanogaster was used in the study to examine the neuroprotective effects of Annona reticulata Linn. leaf extract against Paraquat-induced neurotoxicity. As per the results of the phytochemical analysis, the Annona reticulata Linn aqueous leaf extract included many phytochemicals like flavanones, phenols, steroids, quinones, coumarins, and flavonoids. Pursuit a toxicity test on the Drosophila melanogaster Oregon R strain, the aqueous extract's antioxidant and neuroprotective activities were evaluated after choosing the ideal paraquat concentration to cause neurodegeneration in the flies. The extract improved the survival rates and greatly decreased locomotor impairment in the treated flies. Additionally, it demonstrated beneficial modulatory effects on the activity of antioxidant enzymes as well as ameliorative effects on the levels of oxidative stress indicators. However, further study is needed to fully understand the molecular pathways behind the extract's neuroprotective activity and to investigate its potential applicability as a medication.